Spatiotemporal Localization of Rab20 in Live RAW264 Macrophages during Macropinocytosis - Egami, Youhei (Japan Society of Histochemistry and Cytochemistry, 2012)
Rab20 is a member of the Rab GTPase family, but its implication in macropinocytosis is unclear. We examined the spatiotemporal localization of Rab20 in RAW264 macrophages by the live-cell imaging of fluorescent protein-fused Rab20. It was shown that Rab20 was transiently associated with macropinosomal membranes. During the early stage of macropinosome formation, Rab20 was slightly localized on the circular ruffles (macropinocytic cups), the precursor forms of macropinosomes, and was increasingly recruited to the newly formed macropinosomes. Although Rab20 was colocalized with Rab5 and Rab21 on macropinosomal membranes, the association of Rab20 with macropinosomes persisted even after the dissociations of Rab5 and Rab21 from macropinosomal membranes. Rab20 was then colocalized with Rab7 and Lamp1, late endosomal/lysosomal markers, on macropinosomes for a while. Our data indicate that Rab20 is a novel component of macropinocytic pathway and functions at long-standing stages from early to late macropinosome maturation.